The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1039/c0cc04395h
|View full text |Cite
|
Sign up to set email alerts
|

Diketopyrrolopyrrole as a p-channel organic semiconductor for high performance OTFTs

Abstract: A new diketopyrrolopyrrole derivative 1 exhibits excellent hole mobilities of 0.7 cm(2) V(-1) s(-1) and a current on/off ratio of 10(6) under ambient conditions in bottom-gate, top-contact organic thin film transistors (OTFTs) fabricated by vacuum deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 29 publications
1
66
0
Order By: Relevance
“…Additionally, owing to their reversible redox behaviour, these chromophores recorded different hyperpolarizability values in each of the two redox states and a high on/off (β on /β off ) ratio. Among the various known acceptors such as thiazole, 32 and benzodiazthiazole, 33 diketopyrrolopyrrole unit [34][35][36] has emerged a promising candidate for optoelectronics 37 and organic photovoltaics 34,38 such as organic light emitting diodes (OLEDs), [39][40][41] organic field effect transistors (OFETs), [42][43][44] organic solar cells (OSCs), [45][46][47] dye sensitized solar cells (DSSCs) [48][49] etc. This sub-unit has two amide groups that make it a strong acceptor, and consequently the energy of the lowest unoccupied molecular orbital (LUMO) of D-A or D-π-A systems, wherein appropriately substituted diketopyrrolopyrrole is used as acceptor, is considerably lowered.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, owing to their reversible redox behaviour, these chromophores recorded different hyperpolarizability values in each of the two redox states and a high on/off (β on /β off ) ratio. Among the various known acceptors such as thiazole, 32 and benzodiazthiazole, 33 diketopyrrolopyrrole unit [34][35][36] has emerged a promising candidate for optoelectronics 37 and organic photovoltaics 34,38 such as organic light emitting diodes (OLEDs), [39][40][41] organic field effect transistors (OFETs), [42][43][44] organic solar cells (OSCs), [45][46][47] dye sensitized solar cells (DSSCs) [48][49] etc. This sub-unit has two amide groups that make it a strong acceptor, and consequently the energy of the lowest unoccupied molecular orbital (LUMO) of D-A or D-π-A systems, wherein appropriately substituted diketopyrrolopyrrole is used as acceptor, is considerably lowered.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported a p-channel, symmetrically functionalized (with thiophenyl group) molecular DPP derivative for OFETs with a highest hole mobility of 0.4 cm 2 /Vs [17]. Suraru et al has also reported a p-channel small molecular DPP derivative functionalized with cyanyl group for OFETs with field-effect mobility of 0.7 cm 2 /Vs [18]. OFETs based on n-channel DPP-T-DCV (functionalized with dicyanovinyl group) has been reported by Yoon et al with an electron mobility of 0.96 cm 2 /Vs (single crystalline) and 0.64 cm 2 /Vs (film) [19].…”
Section: Introductionmentioning
confidence: 96%
“…The 1,4-diketo-3,6-diphenylpyrrolo [3,4-c]pyrrole (DPP) derivatives have excellent chemical, thermal and photochemical stabilities and have attracted wide attention in the field of functional materials such as field-effect transistor [35][36][37][38] and polymer solar cells [39][40][41]. On the one hand, unmodified DPP emits green fluorescence but it can reach the near-infrared region after modification.…”
Section: Introductionmentioning
confidence: 99%